2000
DOI: 10.1038/35002510
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for recognition and repair of the endogenous mutagen 8-oxoguanine in DNA

Abstract: Spontaneous oxidation of guanine residues in DNA generates 8-oxoguanine (oxoG). By mispairing with adenine during replication, oxoG gives rise to a G x C --> T x A transversion, a frequent somatic mutation in human cancers. The dedicated repair pathway for oxoG centres on 8-oxoguanine DNA glycosylase (hOGG1), an enzyme that recognizes oxoG x C base pairs, catalysing expulsion of the oxoG and cleavage of the DNA backbone. Here we report the X-ray structure of the catalytic core of hOGG1 bound to oxoG x C-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
1,019
4
5

Year Published

2000
2000
2006
2006

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 916 publications
(1,066 citation statements)
references
References 43 publications
(36 reference statements)
38
1,019
4
5
Order By: Relevance
“…8-oxodG is known to cause DNA misreplication resulting in mutation or cancer (19,20). Catechol increased the amount of 8-oxodG in HL-60, whereas the amount of 8-oxodG in HP100 was not increased.…”
Section: The Role Of Reactive Oxygen Species In Carcinogenesismentioning
confidence: 96%
“…8-oxodG is known to cause DNA misreplication resulting in mutation or cancer (19,20). Catechol increased the amount of 8-oxodG in HL-60, whereas the amount of 8-oxodG in HP100 was not increased.…”
Section: The Role Of Reactive Oxygen Species In Carcinogenesismentioning
confidence: 96%
“…Formation of 8-oxodG causes DNA misreplication, which can lead to mutation, particularly G3 T substitution. 14,15 To investigate whether estrogens and their metabolites are more important in tumor promotion, we examined the effects of estradiol and catechol estrogens on proliferation of estrogen-dependent MCF-7 cells, derived from human breast-cancer cells.…”
mentioning
confidence: 99%
“…The hOGG1 molecule can recognize 8-OHdG, and then catalyse both the release of 8-OHdG and the cleavage of DNA at the resulting apurinic site. 21 The enzyme itself is very sensitive to UVB irradiation, which causes photolysis of tryptophan residues at the active site and leads to hOGG1 inactivation. 30 It has been demonstrated that a CG polymorphism at nucleotide position 1245 in exon 7 of the hOGG1 gene results in an amino-acid substitution from serine to cysteine at residue 326.…”
Section: Discussionmentioning
confidence: 99%
“…The human 8-oxoguanine glycosylase I (hOGG1) is the key component responsible for the removal of 8-OHdG in DNA. 21 Previous genetic studies have revealed the presence of several polymorphisms within the hOGG1 locus. 22,23 Among them, a common polymorphism has been shown to have a functional difference.…”
Section: Introductionmentioning
confidence: 99%